Whole-Body Vibration Partially Reverses Aging-Induced Increases in Visceral Adiposity and Hepatic Lipid Storage in Mice. - Aaffien C Reijne; Jolita Ciapaite; Theo H van Dijk; Rick Havinga; Eddy A van der Zee; Albert K Groen; Dirk-Jan Reijngoud; Barbara M Bakker; Gertjan van Dijk (PLoS ONE, 2016)
At old age, humans generally have declining muscle mass and increased fat deposition, which can increase the risk of developing cardiometabolic diseases. While regular physical activity postpones these age-related derangements, this is not always possible in the elderly because of disabilities or risk of injury. Whole-body vibration (WBV) training may be considered as an alternative to physical activity particularly in the frail population. To explore this possibility, we characterized whole-body and organ-specific metabolic processes in 6-month and 25-month old mice, over a period of 14 weeks of WBV versus sham training. WBV training tended to increase blood glucose turnover rates and stimulated hepatic glycogen utilization during fasting irrespective of age. WBV was effective in reducing white fat mass and hepatic triglyceride content only in old but not in young mice and these reductions were related to upregulation of hepatic mitochondrial uncoupling of metabolism (assessed by high-resolution respirometry) and increased expression of uncoupling protein 2. Because these changes occurred independent of changes in food intake and whole-body metabolic rate (assessed by indirect calorimetry), the liver-specific effects of WBV may be a primary mechanism to improve metabolic health during aging, rather than that it is a consequence of alterations in energy balance.